Human Resource Management Strategies in Improving Lecturer Performance in Higher Education - Lili Fadli Muhamad (Indo-MathEdu Intellectuals Journal, 2023)
Higher education has a very important role in the development of society and the progress of a country. In the higher education environment, the role of lecturers or teachers is crucial in creating a quality learning experience for students. This study aims to examine how human resource management can play a role in improving lecturer performance in higher education. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The results of the study show that regular and continuous evaluation of human resource management strategies is an important stage in adjusting and improving the approach applied. This allows higher education institutions to continue to grow and ensure that their lecturers have maximum support in an effort to provide quality education and improve the institution's reputation